Aliovalent Sm-doping enables BNT-based realxor ferroelectric ceramics with > 90% energy efficiency - Dong-Xu Li; Wei Deng; Zong-Yang Shen; Zhipeng Li; Xiaojun Zeng; Xuhai Shi; You Zhang; Wenqin Luo; Fusheng Song; Chao-Feng Wu (Journal of Advanced Ceramics)
Dielectric capacitors, as physical powers, are critical components of advanced electronics and pulse power systems. However, achieving high energy efficiency without sacrificing recoverable energy density remains a challenge for most dielectric materials. In this work, the aliovalent Sm3+ doped Ba0.12Na0.3Bi0.3Sr0.28TiO3 (BNBST) relaxor ferroelectric at the A site was used to design a defect-induced phase/domain structure to improve polarization switching. A high energy efficiency of 91%, together with a recoverable energy density of 2.1 J/cm3, was achieved in Sm0.07–BNBST ceramics at a low electric field of 114 kV/cm, exceeding those of other dielectric materials under the same electric field. In addition, Sm0.07–BNBST ceramics exhibit good energy storage stability and endurance and fast charging‒discharging speeds, demonstrating their great potential in electrostatic capacitor applications. This work provides an approach to achieve high-performance dielectrics through aliovalent rare earth doping and builds a close relationship between the defect-engineered phase/domain structure and polarization switching for energy storage.